N4-Acetylcytidine enhances synthetic mRNA translation yield and fidelity - Sarah Schiffers; Blake W. Nelson; Maria Prigge; Shriya Krishna; Leslie Watkins; Yining Zhu; Nishu Tyagi; Hamid Beiki; Sudipto Das; Ayush Raman; Jingyao Ma; Thorkell Andresson; et al. (Nature, 2026)
Abstract Synthetic mRNA therapeutics offer a versatile platform for treating diverse conditions, including cancer and infectious diseases. For delivery into cells, these mRNAs are encapsulated in lipid nanoparticles and commonly incorporate modified ribonucleotides to improve stability, enhance translation and mitigate immune recognition 1 . N 1 -Methylpseudouridine (m 1 Ψ) has become the industry standard for synthetic mRNAs owing to its effectiveness in promoting translation and reducing immunogenicity 2 . However, recent studies have shown that m 1 Ψ can compromise translational fidelity, leading to errors such as premature termination and ribosomal frameshifting 3–5 . Here we reveal N 4 -acetylcytidine (ac 4 C) as a functionally distinct alternative to m 1 Ψ. Across cultured cell lines, primary human monocyte-derived dendritic cells and mouse liver, ac 4 C suppressed inflammatory responses as effectively as m 1 Ψ while driving higher protein yields. Single-molecule imaging of translation revealed broadly similar ribosome densities per mRNA for ac 4 C-modified and m 1 Ψ-modified transcripts. However, translation elongation with m 1 Ψ-modified mRNA was nearly twofold slower than with ac 4 C, which resulted in reduced protein output and increased ribosome collisions that further limited protein production through the engagement of quality-control pathways and +1 frameshifting. These findings underscore the importance of context in designing therapeutic mRNAs and position the translation elongation rate as a key determinant of the efficacy of modified ribonucleotides.